2020
DOI: 10.5423/ppj.oa.02.2020.0028
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Application of Bacillus Strains Isolated from Nonrhizospheric Rice Soil for the Biocontrol of Rice Blast

Abstract: Rice blast, caused by Magnaporthe oryzae, is one of the most destructive rice diseases worldwide. The aim of this study was to screen bacterial isolates to efficiently prevent the occurrence of rice blast. A total of 232 bacterial isolates were extracted from nonrhizospheric rice soil and were screened for antifungal activity against M. oryzae using a leaf segment assay. Strains S170 and S9 showed significant antagonistic activity against M. oryzae in vitro and in leaf disk assays, and controlled M. oryzae inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
(36 reference statements)
1
13
0
Order By: Relevance
“…Currently, there have been numerous reports about the antagonistic effects and biocontrol efficacies of B. velezensis strains on M. oryzae, some of which were registered as the bacterial pesticides used in rice production (Chen et al, 2021). From our dual culture tests, B. velezensis BR-01 has an 83.7% relative inhibition rate on M. oryzae, which is comparable to most of other B. velezensis strains on M. oryzae (Sha et al, 2020;Chakraborty et al, 2021). B. velezensis BR-01 also showed antifungal activity against U. virens and F. fujikuroi, with relative inhibition rates 96.6 and 57.9%, respectively.…”
Section: Discussionsupporting
confidence: 53%
“…Currently, there have been numerous reports about the antagonistic effects and biocontrol efficacies of B. velezensis strains on M. oryzae, some of which were registered as the bacterial pesticides used in rice production (Chen et al, 2021). From our dual culture tests, B. velezensis BR-01 has an 83.7% relative inhibition rate on M. oryzae, which is comparable to most of other B. velezensis strains on M. oryzae (Sha et al, 2020;Chakraborty et al, 2021). B. velezensis BR-01 also showed antifungal activity against U. virens and F. fujikuroi, with relative inhibition rates 96.6 and 57.9%, respectively.…”
Section: Discussionsupporting
confidence: 53%
“…This activity may induce cell wall damage and degradation. Sha et al (2020) reported that P. oryzae P131 cells treated with Bacillus pumilus strain S9 and Bacillus amyloliquefaciens strain S170 had peculiar cell morphology and disruption, indicating that they degrade the cell walls, destroy cell membranes, and damage cellular organelles. In the measurement of chitinase, the standard curve created by NAG was used to determine the reducing sugar concentration of NAG released in colloidal chitinsupplemented medium (Agrawal and Kotasthane 2012).…”
mentioning
confidence: 99%
“…B. velezensis CE 100 could simultaneously control Phytophthora root rot diseases and enhance growth of Chamaecyparis obtusa seedlings [ 13 ]. Bacillus amyloliquefaciens S170 and B. pumilus S9 isolated from nonrhizospheric rice soil showed significant antagonistic activity against M. oryzae in vitro and in leaf disk assays [ 15 ]. Zhou found Bacillus cereus YN917, obtained from a rice leaf with remarkable antifungal activity against M. oryzae , and exhibited multiple plant growth-promoting and disease prevention traits [ 16 ].…”
Section: Introductionmentioning
confidence: 99%